2022
DOI: 10.21272/mmi.2022.1-19
|View full text |Cite
|
Sign up to set email alerts
|

Financial Innovation Management: Impact of Fiscal Decentralization on Economic Growth of the Baltic Countries

Abstract: The management process of fiscal policy incorporates a wide analysis of various factors. The dynamic financial approach should be applied in deciding the level of centralization. The article offers the usage of the multicriteria method in selecting fiscal variables as a new instrument for financial evolution. In this article, the hypothesis of decentralization's impact on economic growth is tested to show the growth opportunities. The implications of the fiscal decentralization index on economic growth across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Global transformation requires a significant scale of state support for the energy sector, the creation of clusters of companies in the field of renewable energy, and the involvement of international donors and public-private partnership programs [46]. In the cases of implementation of complex projects related to renewable energy production, only direct state support can be a guarantee of ecological development, given the insufficient financial resources of individual regions or companies [47]. It was previously empirically confirmed that the strategy of financial support for the development of renewable energy must consider the energy needs of the territory, its natural and resource base, and the installed capacity of renewable energy facilities and their economic potential [48].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Global transformation requires a significant scale of state support for the energy sector, the creation of clusters of companies in the field of renewable energy, and the involvement of international donors and public-private partnership programs [46]. In the cases of implementation of complex projects related to renewable energy production, only direct state support can be a guarantee of ecological development, given the insufficient financial resources of individual regions or companies [47]. It was previously empirically confirmed that the strategy of financial support for the development of renewable energy must consider the energy needs of the territory, its natural and resource base, and the installed capacity of renewable energy facilities and their economic potential [48].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The implementation of eco-innovation in eco-organizations includes co-training programs, eco-product design programs, the introduction of eco-learning techniques, the creation of management teams to deal with eco-issues, and eco-management systems [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In part, this happened because by solving these problems the countries can provide their national economies with their own financial resources, obtain additional income from the export of financial resources to other countries, and counter the threats of global financial risks. This is evidenced by the increase in the number of strategic plans for the financial development of countries [ 1 – 13 ] and the number of scientific publications [ 14 29 ] on this topic. However, an analysis of strategic plans shows that their main goal is to develop the financial sector of national economies without taking into account the systemic risks of this development.…”
Section: Introductionmentioning
confidence: 99%